Budidaya Sayur Melalui Kegiatan Pendampingan Sebagai Upaya Mewujudkan Program Ketahanan Pangan - Khasanah, Fata Nidaul; Untari, Dhian Tyas; Susanto, Ibnu; Nurmanto, David (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
One of the efforts to support the availability of food, especially vegetables as a provider of healthy family nutrition during a pandemic, is to use yards for the cultivation of various types of plants. One of the activities that can be done is to carry out vegetable cultivation activities. The partner of this activity is South Tambun village RT 04. The location of the partner has a yard but is felt to be less than optimal related to its utilization. The condition of the yard so far has not contributed to the fulfillment or support of daily needs. Furthermore, the yard so far, in addition to not contributing added value to the fulfillment of daily needs, also does not provide comfort and beauty. If the yard is arranged and empowered, it is expected to add aesthetic value and contribute to the needs of the community, especially vegetables for daily consumption. So that the arrangement and utilization of the yard as one solution that can contribute to daily needs, especially vegetables. The implementation of activities starts from counseling, training, mentoring and evaluation. Training begins with spreading vegetable seeds, followed by care and harvesting. Evaluation of activities related to enthusiasm and satisfaction from service activities that have been carried out reaches 92%.